PELATIHAN PRODUKSI MEDIA ONLINE UNTUK MENINGKATKAN KAPASITAS SISWA SMK 3 PERGURUAN CIKINI - Alamsyah Alamsyah; Agus Hitopa Sukma; Misnan Misnan; Alfan Bachtiar; Iswahyu Pranawukir; Fikry Suandi (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2024)
This Community Service Program aims to improve the skills of SMK 3 Cikini College students in online media production. The implementation method includes technical training ranging from pre-production to post-production of digital content. The results of the activity showed an improvement in students' skills in producing quality online media content, with a sustainability impact in supporting students' abilities in the digital era.